PARTISIPASI MASYARAKAT DALAM PENGELOLAAN KAMPU ADAT DESA KARANG BAJO KECAMATAN BAYAN KABUPATEN LOMBOK UTARA - Vitri Millenia Tata Maisyani; Siluh Putu Damayanti; Agusman Agusman (Journal Of Responsible Tourism, 2022)
The problems studied in this study are related to community participation in the management of the traditional village of Karang Bajo, Bayan District, North Lombok. The purpose of this study was to describe the participation of the community in Karang Bajo village in managing the traditional village. The research method used is descriptive qualitative with the research location in the traditional village of Karang Bajo village. Data collection techniques used in-depth interviews with observation techniques related to community participation. Data analysis techniques used are data reduction, presentation, data analysis, and drawing conclusions. Vertical participation is marked by the presence of outsiders who become leaders in involving the role of the community such as indecon from NGO, AMAN, KOMPAK, Rinjani Lodge, Institutions (STP Mataram, Unram, UIN Mataram, UGM) PT Bali Nusra and the local government. Horizontal participation is characterized by the role of the community in managing things or activities that are formed between the communities themselves in the form of mutual cooperation, deliberation and consensus and so on. Meanwhile, physical participation in Karang Bajo village refers to the form of the community's role in the form of objects that can be seen in the construction of traditional schools and the manufacture of art houses as olshops for community crafts. Non-physical participation found is community participation in the form of ideas or ideas in the management of Traditional Kampu in Karang Bajo village which can be seen in the ideas of a number of outside parties on vertical participation (partners) on tourism counseling, tourism management training, assistance in the preparation of tour packages and so on.